The Learning of Multigraded Mexican Schools in Planea - Eduardo Hernández Padilla (Universidad Autónoma de Madrid, 2018)
Demographic situation, and the lack of educational policies attending to vulnerable populations have led to large educational gaps to which are subjected to thousands of children. The National Educational System grants a solution through the creation of multigrade schools to address this problem, where one school teacher teaches to two grades or more. Several studies report that children who attend these schools have an academic performance below the students of regular schools; however, these works do not evaluate quantitatively and large scale the knowledge of basic learning in education. This study evaluated some factors that influence the learning of the academic achievement according to the research of educational evaluation, of the students in multigrade schools, in Planea with 8104 students from 838 multigrade schools. The hierarquical linear modeling was employed for the analysis of the information. The outcomings exhibit differential effects of the factors; some of them affected the academic achievement; whereas, anothers, important according to others studies, they were not meaningful. The results show the influence of some factors recognized in the state; meanwhile another important variable was not significant. These results can be attributed to the limited information collected in that background questionnaires.